THE INFLUENCE OF WORK ABILITY AND SELF-ACTUALIZATION ON EMPLOYEES' WORK ETHIC AT THE COMMUNICATION AND INFORMATICS DEPARTMENT OF CENTRAL TAPANULI REGENCY - Rifani Ana Tasya Sinaga; Nelly Azwarni Sinaga; Sahat Simatupang (Patua : Journal of Business Administration and Management, 2025)
The purpose of this study was to determine the partial effect of work ability and self-actualization on the work ethic of employees at the Communication and Informatics Office of Central Tapanuli Regency. This research was descriptive and quantitative, using a saturated sample of 42 employees. Data were analyzed using multiple linear regression analysis. Based on the research findings, it was found that work ability and self-actualization had a 61.4% effect on work ethic, while the remaining 38.6% was influenced by other factors not examined in the study. Work ability and self-actualization had an effect on work ethic, with the calculated F (33.676) being greater than the F (3.22). Work ability had an effect on work ethic, with the calculated t value of 3.249 being greater than the calculated t value of 2.018. Work involvement had an effect on work ethic, with the calculated t value of 3.314 being greater than the calculated t value of 2.018. The positive sign in the multiple linear regression equation, Y = 4.919 + 0.439 X1 + 0.457 X2, indicates that work ethic will increase if employee work ability and self-actualization are good.